Acute Myocardial Infarction: The First Manifestation of Ischemic Heart Disease and Relation to Risk Factors - Manfroi,Waldomiro Carlos (2002)
OBJECTIVE: To assess the association between cardiovascular risk factors and acute myocardial infarction as the first manifestation of ischemic heart disease, correlating them with coronary angiographic findings. METHODS: We carried out a cross-sectional study of 104 patients with previous acute myocardial infarction, who were divided into 2 groups according to the presence or absence of angina prior to acute myocardial infarction. We assessed the presence of angina preceding acute myocardial infarction and risk factors, such as age >55 years, male sex, smoking, systemic arterial hypertension, lipid profile, diabetes mellitus, obesity, sedentary lifestyle, and familial history of ischemic heart disease. On coronary angiography, the severity of coronary heart disease and presence of left ventricular hypertrophy were assessed. RESULTS: Of the 104 patients studied, 72.1% were males, 90.4% were white, 73.1% were older than 55 years, and 53.8% were hypertensive. Acute myocardial infarction was the first manifestation of ischemic heart disease in 49% of the patients. The associated risk factors were systemic arterial hypertension (RR=0.19; 95% CI=0.06-0.59; P=0.04) and left ventricular hypertrophy (RR=0.27; 95% CI=0,.8-0.88; P=0.03). The remaining risk factors were not statistically significant. CONCLUSION: Prevalence of acute myocardial infarction as the first manifestation of ischemic heart disease is high, approximately 50%. Hypertensive individuals more frequently have symptoms preceding acute myocardial infarction, probably due to ventricular hypertrophy associated with high blood pressure levels.